2013
DOI: 10.5271/sjweh.3376
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work characteristics and sleep quality: a systematic review of longitudinal and intervention research

Abstract: We were especially interested in the causal relations between psychosocial work characteristics and sleep quality and therefore this review focuses on longitudinal and prospective intervention studies. Moreover, the quality criteria developed for this review constitute a valuable and practical checklist for designing future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 56 publications
(152 reference statements)
7
105
0
5
Order By: Relevance
“…However, appraisals of studies largely involved synthesizing quantitative information directly from publications and every effort has been made to ensure accuracy and consistency in the review process. Also, central to the current review, study ratings were determined by a clear set of decision rules that have been successfully applied in systematic reviews on similar topics (47)(48)(49).…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, appraisals of studies largely involved synthesizing quantitative information directly from publications and every effort has been made to ensure accuracy and consistency in the review process. Also, central to the current review, study ratings were determined by a clear set of decision rules that have been successfully applied in systematic reviews on similar topics (47)(48)(49).…”
Section: Study Limitationsmentioning
confidence: 99%
“…There is growing evidence of the negative effects of work stress on sleep (1). Problems with restorative sleep are common: chronic insomnia has a 10% prevalence rate in Western industrialized countries (2)(3)(4).…”
mentioning
confidence: 99%
“…However, the relation between work stressors and sleep remains unclear. A recent review identified high job demands and low job control as predictors of reduced sleep quality, but effect sizes were small-to-moderate indicating that only a small proportion of the variance in sleep quality is influenced by work characteristics (15). Additionally, researchers have drawn attention to discrepancies between objective and subjective sleep measures and the risk of overestimating the effect of work stressors on sleep quality in studies using self-reported sleep measures (27,28).…”
Section: Sleep Stress and Workmentioning
confidence: 99%
“…Sleep problems are prevalent in modern society (10) and have been associated with a broad spectrum of negative health outcomes (11)(12)(13)(14)(15)(16)(17)(18)(19). Stress is a common selfreported cause (20).…”
Section: Sleep Stress and Workmentioning
confidence: 99%